Pulmonary function and body composition parameters of children with cystic fibrosis from a hight complexity institution between 2015 and 2018 - Aura María Salazar-Solarte; Laura Torres-Canchala; Frank Carrera-Gil; Diana María Quimbayo-Wilches (Elsevier, 2024)
Background: An adequate nutritional status in patients with cystic fibrosis correlates with higher survival and better pulmonary function. Body mass index (BMI) is an anthropometric indicator with independent association with pulmonary function, and it can hide alterations of nutritional status in cystic fibrosis. Objective: To determine the relationship of lung function with BMI and body composition parameters in children with cystic fibrosis in a Hight Complexity institution between 2015 and 2018. Materials and methods: It was an observational study with analytical, cross-sectional, and retrospective scope, including 33 patients between 5 and 17 years old. Spearman's test was applied to evaluate correlation of FEV1 (forced expiratory volume in first second) with BMI and five body composition parameters by bioelectrical impedance using InbodyS10 equipment. Statistical significance was considered with p < 0.05. Results: Positive correlation was obtained between FEV1 and appendicular skeletal muscle mass between lung function and percentage of fat-free mass (p = 0.006) and phase angle (p = 0.001). Percent fat mass had a negative correlation with FEV1 (p = 0.007). BMI and fat free mass index did not correlate with lung function (p = 0.085). Conclusions: Appendicular skeletal muscle mass correlated better than BMI with lung function in children with cystic fibrosis. It is recommended to perform anthropometric follow-up by BMI complemented with body composition study in children with cystic fibrosis. Analyses with larger populations are required to standardize its use.